Katolicy i prawosławni w anegdocie kresowej z przełomu XIX i XX wieku. Kilka refleksji o historii zawartej w ówczesnym humorze i dowcipie - Jurkowski, Roman (Przegląd Wschodnioeuropejski, 2023)
The article is an attempt to determine to what degree historical anecdotes can be used in scientific historical research. Several selected anecdotes relating to denominational and religious issues occurring in the Taken Lands at the end of the 19th and at the beginning of the 20th century are analyzed. The author shows that this type of information can only be of a supporting nature in scientific research. Nevertheless, they cannot be omitted because they are valuable research material for the personal characteristics of given historical figures.